PENGEMBANGAN SIKAP TOLERANSI MELALUI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN 08 UJAN MAS - Bram Kumbara; Deri Wanto; Hendra Harrmi (ILJ: Islamic Learning Journal, 2023)
Tolerance is the source of the issue in this study. The state of Indonesia is the focus of attention because of its intolerance, which stems from people's differences of opinion and lack of knowledge. This has an effect on changing society's paradigm and attitude, which was once known as an integrated society that has disintegrated. society or can be deciphered as a daily existence that maintains fellowship and resilience. transformed into an individualistic or childish society. This qualitative analysis study, which used both primary and secondary data as its sources, was carried out at SDN 08 Ujan Mas. According to the findings of this study, the role that Islamic education plays in shaping students' attitudes includes: 1) The curriculum and rules of the school, specifically the teaching and learning activities that are related to ethics and religion; ( 2) Sports and cultural activities, specifically social activities like working together. For instance, culture is comparable to participating in extracurricular art activities. Activities that require teamwork, such as soccer, volleyball, basketball, and futsal 3) Group learning, in which students are divided into multiple groups during the teaching and learning process